Analisa Pendapatan Kelompok Tani Desa Taeno di Kota Ambon - Aldi Aldi; Semmy Pesireron; chrestiana Aponno (P3M Politeknik Negeri Ambon, 2024)
This study aims to analyze the income of the Taeno Hamlet farmer group business precisely. It is hoped that farmers can identify the problems faced in order to increase their business income. The difference between income and all costs incurred is income (Soekartawi, 2017). To calculate farm income, what must be known is all expenses and income during the farming business run within the specified time. To calculate farm income, you can use the formula: Y = TR - TC The income of the farmer group from the 4 types of plants produced is IDR 424,930,000 and the total cost incurred is IDR 35,430,000 so that the income obtained is IDR 389,500,000. To further increase agricultural yields, farmers must plant other crops while waiting for the harvest period such as basil, spring onions so that in between the time before waiting for the main crop harvest, farmers will get results from other crops. Farmers are advised to sell directly to the market and not through second hands, which causes the selling price to be too low. Keyword :Farmer Income